2022
DOI: 10.3390/ijms232213799
|View full text |Cite
|
Sign up to set email alerts
|

3D Molecular Imaging of Stratum Corneum by Mass Spectrometry Suggests Distinct Distribution of Cholesteryl Esters Compared to Other Skin Lipids

Abstract: The crucial barrier properties of the stratum corneum (SC) depend critically on the design and integrity of its layered molecular structure. However, analysis methods capable of spatially resolved molecular characterization of the SC are scarce and fraught with severe limitations, e.g., regarding molecular specificity or spatial resolution. Here, we used 3D time-of-flight secondary ion mass spectrometry to characterize the spatial distribution of skin lipids in corneocyte multilayer squams obtained by tape str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…The stratum corneum (SC), which provides the barrier function of the skin (Menon et al, 2012), also shows PI(4,5)P2 signal (Figure 1A). This is consistent with the notion of SC being a lipid matrix containing phospholipids (van Smeden et al, 2014a;van Smeden et al, 2014b;Sjovall et al, 2022).…”
Section: Resultssupporting
confidence: 91%
“…The stratum corneum (SC), which provides the barrier function of the skin (Menon et al, 2012), also shows PI(4,5)P2 signal (Figure 1A). This is consistent with the notion of SC being a lipid matrix containing phospholipids (van Smeden et al, 2014a;van Smeden et al, 2014b;Sjovall et al, 2022).…”
Section: Resultssupporting
confidence: 91%
“…One key advantage of ToF-SIMS in metabolomics is its versatility in detecting various metabolites, such as amino acids, lipids, sugars, and nucleotides ( Marzec et al, 2022 ; Noun et al, 2022 ; Sjövall et al, 2022 ). This capability has been demonstrated in several studies, where ToF-SIMS was applied to visualize the metabolites in different cell types and identify potential biomarkers for cell type classification, such as unsaturated diacylglycerol, oleic acid, and linoleic acid, in combination with immunofluorescence ( Song et al, 2020 ).…”
Section: Bioimaging Applications In Tof-simsmentioning
confidence: 99%
“…In the study published herein, Sjövall et al [ 100 ] have demonstrated the possibility of determining the molecular composition of superficial layers in stratum corneum, and the spatial distribution of specific lipids using three-dimensional time-of-flight secondary ion mass spectrometry. Thus, this technique could be used to expand the knowledge regarding the skin barrier, and to evaluate the effects of different active pharmaceutical ingredients, cosmetic molecules, or penetration enhancers in relation to this cutaneous function.…”
mentioning
confidence: 99%